Cashew (Anacardium occidentale L.) Nuts Modulate the Nrf2 and NLRP3 Pathways in Pancreas and Lung after Induction of Acute Pancreatitis by Cerulein - Marika Cordaro; Roberta Fusco; Ramona D'Amico; Rosalba Siracusa; Alessio Filippo Peritore; Enrico Gugliandolo; Tiziana Genovese; Rosalia Crupi; Giuseppina Mandalari; Salvatore Cuzzocrea; Rosanna Di Paola; Daniela Impellizzeri (MDPI AG, 2020)
Background: One of the most common co-morbidities, that often leads to death, associated with acute pancreatitis (AP) is represented by acute lung injury (ALI). While many aspects of AP-induced lung inflammation have been investigated, the involvement of specific pathways, such as those centered on nuclear factor E2-related factor 2 (Nrf2) and nucleotide-binding domain leucine-rich repeat (NLR) and pyrin domain containing receptor 3 (NLRP3), has not been fully elucidated. Methods: To investigate the effect of cashew (Anacardium occidentale L.) nuts on pancreatic and lung injury induced by cerulein injection, cerulein (50 μg/kg) was administered to CD1 mice for 10 h. Oral treatment with cashew nuts at a dose of 100 mg/kg was given 30 min and 2 h after the first cerulein injection. One hour after the final cerulein injection, mice were euthanized and blood, lung and pancreatic tissue samples were collected. Results: Cashew nuts were able to (1) reduce histological damage; (2) mitigate the induction of mast cell degranulation as well as the activity of myeloperoxidase and malondialdehyde; (3) decrease the activity levels of amylase and lipase as well as the levels of pro-inflammatory cytokines; and (4) enhance the activation of the Nrf2 pathway and suppress the activation of the NLRP3 pathway in response to cerulein in both pancreas and lung. Conclusions: Cashew nuts could have a beneficial effect not only on pancreatitis but also on lung injury induced by cerulein.